Pengenalan Alat Peraga Dasar Matematika Kepada Siswa Sekolah Dasar (SD) - Irvana Arofah; Besse Arnawisuda Ningsi (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Community service is carried out by the Pamulang University lecturer team in Pamulang sub-district, South Tangerang city in an effort to increase understanding of mathematical concepts with the target of elementary school students. The activities carried out are divided into 3 stages, the first stage: first giving a pre-test to students to find out the students' initial abilities, the second stage providing mentoring and training in understanding mathematical counting concepts with the help of mathematical teaching aids, and the third stage conducting evaluations with how to give a test (post-test) to determine the results of the treatment in the second stage. The visual aids used in this activity are the nomographic aids, the visual aids weighing the car props. Each of these props provides an understanding of the mathematical counting concepts in the operations of addition, subtraction, multiplication and division. From the results of the post-test conducted an increase in students' understanding of the concepts of mathematical operations in the form of operations of addition, subtraction, multiplication and division after being given understanding with the help of mathematical teaching aids.